Mechanisms of regulation of the internal environment and health (Eurasian Journal of Ecology, 2016)
On the homeostasis or internal environment of researchers holding on this issue before sihpor no consensus. In data time the concept of " internal environment " in the scientific literature on the biology, medicine is fully engaged. For example there is the concept of " external environment" – is the environment around us , in other ecological environment wherewe live , and the " internal environment " of its elements . Therefore, there is a constant between these, durable bond, where share their border epithelial membranes. Therefore, different specialists , anatomy, morphology , philosophy and psychology provide " internal environment" different definitions.
Keywords: homeostasis; of the internal environment; mechanism; hypertension; barroretseptor; osmosis; irritant; absolute equality; temperature; microevolution.